An uncommon cause of sciatic pain: tuberculous osteomyelitis of the ischial tuberosity. Issue 5 (3rd September 2017) - De Mulder, Pieter; Harth, Charlotte; Ide, Louis; Vallaeys, Jurgen; Baelde, Nick; De Bo, Thomas
Abstract : A 66-year-old Caucasian female presented with insidious sciatic pain leading to an uncommon diagnosis of tuberculous osteomyelitis with unknown portal entry. The patient did not report a history of a previous tuberculosis (TB) infection and her chest X-ray was negative for TB. Considering TB in the differential diagnosis of a 'bone abscess', it is of paramount importance to come to a correct diagnosis. Conventional radiographs still remain the first-line imaging modality for evaluation of skeletal symptomatology. However, biopsies or aspirates are often needed to yield the definitive diagnosis. The lack of awareness of the potential extrapulmonary involvement of TB leads to an important delay in diagnosis and treatment. Antituberculous drugs should be started at the time of biopsy and continued during 12–18 months, due to poor drug penetration into osseous and fibrous tissues.